COVID-19 vaccine acceptance among pregnant women in Hospital USM - Zaid, Siti Nur Aisyah (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2022)
Incentive spirometry is a device used to measure the volume of the air inhaled into the lungs during inspiration. A cross-sectional study has been conducted to determine the knowledge of lung expansion implementing incentive spirometry. This study also examines the difference of knowledge of score of incentive spirometry between degree and diploma of nursing students and the correlation between clinical experience and knowledge of score of incentive spirometry among degree and diploma of nursing students. Independent t-test was used to identify the difference of knowledge of score of incentive spirometry between degree and diploma of nursing students. Pearson’s correlation test was used to determine correlation between clinical experience and knowledge of score of incentive spirometry among degree and diploma of nursing students. A total of 181 nursing students, 76 students were Bachelor of Nursing, and 105 students were from Diploma in Nursing were recruited through stratified sampling. Data were collected from March 2022 until May 2022 using google form and analyzed using SPSS version 26.0 for a window. The results revealed degree and diploma of nursing students have same knowledge regarding incentive spirometry as there was no mean difference in knowledge of score of incentive spirometry (p-value=0.166). There was no correlation to be found between clinical experience and knowledge of score of incentive spirometry between degree and diploma of nursing students (p-value= 0.091). In conclusion, both degree and diploma of nursing students has good knowledge regarding incentive spirometry.